MUCORMYCOSI (BLACK FUNGUS): A REVIEW - SINGH, GAGANDEEP; SINGH, NARINDER; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2021)
Mucormycosis is a new angioinvasive infection caused by the ubiquitous filamentous fungus of the Mucorales order of the Zygomycete class. Mucormycosis has emerged as the third most prevalent invasive mycosis in patients undergoing hematological and allogeneic stem cell transplantation, following candidiasis and aspergillosis. Sporangiospores must be inhaled on a daily basis. Members of the Mucorales are very infrequent in nasal mucus, indicating that spores in airway mucus are removed via mucociliary transport or that there is a minimal degree of airborne contamination.